2008
DOI: 10.1590/s0102-09352008000200024
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de nutrientes em frangos alimentados com dietas suplementadas com fitase e níveis reduzidos de fósforo não-fítico

Abstract: Avaliaram-se a digestibilidade ileal, retenção de nutrientes e valores de energia metabolizável aparente (EMA) de dietas suplementadas com fitase e níveis reduzidos de fósforo não-fítico (FNF) para frangos de corte. Foram utilizados 330 pintos machos em delineamento em blocos ao acaso e esquema fatorial 2 x 3 com dois níveis de fitase (0 e 25U/kg) e três níveis de FNF (100, 85 e 70% das exigências da ave), totalizando seis tratamentos com cinco repetições de 11 aves cada. Não houve efeito da interação FNF vs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Lalpanmawia et al (2014) found improved ileal digestibility coefficients for P with diets supplemented with 500 FTU kg -1 . Oliveira et al (2008) reported increased ileal digestibility coefficients for Ca and P due to the use of phytase, showing that the hydrolysis of the phytate-mineral complex does not only release P but also Ca, ready to be absorbed.…”
Section: Resultsmentioning
confidence: 99%
“…Lalpanmawia et al (2014) found improved ileal digestibility coefficients for P with diets supplemented with 500 FTU kg -1 . Oliveira et al (2008) reported increased ileal digestibility coefficients for Ca and P due to the use of phytase, showing that the hydrolysis of the phytate-mineral complex does not only release P but also Ca, ready to be absorbed.…”
Section: Resultsmentioning
confidence: 99%
“…According to Oliveira et al (2008), the phytase inclusion in the diets was sufficient to increase the crude protein in 7.46% of these diets and the metabolizability of crude protein improved in 2% with the phytase inclusion, regardless to available phosphorus levels. In this work, the phytase supplementation, in 500 PU/kg, in the feed with 0.65% of calcium and 0.325% of available phosphorus, made it possible to enhance the metabolizability coefficient of crude protein up to 4.85%.…”
Section: Resultsmentioning
confidence: 99%